2014
DOI: 10.1080/14926156.2014.990173
|View full text |Cite
|
Sign up to set email alerts
|

Language Repair Strategies in Bilingual Tutoring of Mathematics Word Problems

Abstract: This study explores the language repair strategies (aimed at repairing communication problems) of two bilingual speakers during mathematics word problem tutoring sessions. Bilingual repair was shown to gradually shift from a linguistic to an epistemic focus during problem solving (i.e., communication became more conceptually focused over time). Linguistic repair involved varied translation techniques (literal and free), whereas epistemic repair entailed gradual refinement of specialized mathematical meanings t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…mathematical terminology), and with a distinctive internal organisation (i.e. a textual structure) that can be logically and rationally understood by readers who bring with them expectations, interests, viewpoints, interpretations and prior reading experiences (Oliveira et al, 2015).…”
Section: Mathematics Word Problemsmentioning
confidence: 99%
“…mathematical terminology), and with a distinctive internal organisation (i.e. a textual structure) that can be logically and rationally understood by readers who bring with them expectations, interests, viewpoints, interpretations and prior reading experiences (Oliveira et al, 2015).…”
Section: Mathematics Word Problemsmentioning
confidence: 99%
“…Researchers have found that the academic performance of ELs improves significantly when such linguistic support is incorporated appropriately in the classroom (Pereira & de Oliveira, 2015; Verplaetse & Migliacci, 2017). Further, the greater the second-language support, the smaller the achievement gaps between ELs and their peers (Oliveira et al, 2015; Viesca et al, 2019).…”
Section: Adding Linguistic Support To Maintain Academic Rigormentioning
confidence: 99%
“…Jimenez (2015) visar att elever löser uppgiften på både sitt första-och andraspråk. Genom att studera hur elever resonerar och tänker högt visades att både första-och andraspråket bidrar med verktyg och strategier att lösa en uppgift (se också Oliveira et al, 2015, Esquinca, 2011, Clarkson, 2007, Parvanehnezhad & Clarkson, 2008, en översikt finns i Vahlstedt, 2016). Dessa studier har bedrivits inom matematikämnet men visar på att andraspråkselever utnyttjar språkkunskaper i båda sina språk för att kunna besvara en fråga i en provsituation.…”
Section: Tidigare Forskningunclassified